FAKTOR-FAKTOR KARAKTERISTIK YANG BERPENGARUH TERHADAP PELAKSANAAN PERILAKU HIDUP BERSIH DAN SEHAT DI DESA TANGUNAN KECAMATAN PURI KABUPATEN MOJOKERTO - Irawati, Dian (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2013)
Applying healthy lifestyle (PHBS) are powerful steps to ward off diseases. However, in practice, a simple application of PHBS that impression is not always easy to do. Especially for those who are not accustomed to. In this case, the education of the family is needed (Angels, 2010). In addition, the number of individual activities undertaken to make them forget about health (Ababar, 2008). This study is to determine the characteristics of the factors that influence the execution behavior of clean and healthy household in the village Tangunan Puri Mojokerto. The population in this study were heads of household in the village Tangunan Puri Mojokerto, as many as 676 households. The sample in this study was taken from the head of the family in the village of Puri Mojokerto Tangunan who met the inclusion criteria were as many as 88 heads of families collected by cluster sampling. Data were collected using an instrument check list and analyzed by chi square test .The results showed that most respondents implementing PHBS in the classification of household 2 and 4 as many as 24 people ( 27.3 % ). The results of the chi square test shows that there were effect of age, education, occupation, and income on household PHBS. According to these results should continue to monitor the implementation of PHBS and icrease PHBS competition as part of efforts to improve the evaluation of people's motivation. Keyword: factors, healthy lifestyle (PHBS)